The Influence of Workload, Leadership Style and Work Environment on Job Stress Among Generation Z Employees at PT Bank Negara Indonesia (Persero) Tbk - Suryaningsih, Inten; Astuti Pratminingsih, Sri (DINASTI RESEARCH, 2025)
This research aims to analyze the impact of workload, work environment, and leadership style on job stress. The research used a quantitative method with 80 Gen Z employees as respondents from PT. Bank Negara Indonesia Tbk. The data were analyzed using multiple regression and processed with SPSS. This study offers novelty by focusing on Gen Z employees as the research subjects. The results show that workload significantly affects stress, with high workload, both in terms of quantity and complexity, increasing stress. On the other hand, the work environment was found to have no significant impact on stress, suggesting that internal factors such as workload are more influential in affecting stress levels. Leadership style also significantly affects stress, where supportive leadership styles, such as transformational or participative, reduce stress, while authoritarian leadership with high demands tends to increase stress. This study provides valuable insights for organizations in managing factors that influence work stress and creating a healthier and more productive work environment.